Unitary invariant and residual independent matrix distributions (2009)
ABSTRACT: Define Z13 = A1/2Y A1/2H (A and Y are independent) and Z15 =B1/2 Y B1/2H (B and Y are independent), where Y , A and B follow inverted complex Wishart, complex beta type I and complex beta type II distributions, respectively. In this article several properties including expected values of scalar and matrix valued functions of Z13 and Z15 are derived.